Stroke and stroke mimics: a case of high grade glioma - Argenti, Roberta Wolffenbüttel; Duarte, Juliana Avila; Klaes, Amália Izaura Nair Medeiros; Oliveira, Francine Hehn; Friedrich, Mariangela Gheller; Campos, Lillian Gonçalves; Perez, Juliano Adams; Antunes, Apio Claudio; Martins, Sheila Ouriques; Vedolin, Leonardo Modesti (Clinical and Biomedical Research, 2015)
The clinical diagnosis of acute stroke is inaccurate approximately 10%-30% of the time, which can lead to unnecessary administration of thrombolytic therapy or delays in appropriate therapy. Rapid and accurate neuroimaging triage is essential to guide therapy and exclude mimics. Although many conditions that mimic stroke clinically have imaging appearances that can overlap acute stroke, these conditions can be differentiated in most cases by using a careful pattern-based approach. We describe a case of 67 yo male patient who had a clinic of wakeup stroke and at the first magnetic resonance image (MRI) it was found that was an acute stroke of middle cerebral artery.The patient did not improve and a second MRI revelead a two times growth of the lesion, and the MRI findings were compatible with tumor. At the surgery they found a infiltrative lesion and the anatomopathological exam showed that it was a high grade glioma.The diagnosis of ischemic stroke is often straight forward; however, the clinical diagnosis of acute stroke is inaccurate in many cases. Furthermore, many of these conditions, such as encephalitis, mass lesions, seizures, hypoglycemia, transient global amnesia (TGA),demyelinating disease, drug toxicity, and metabolic disturbances, have imaging appearances that can mimic acute or subacute infarction; however, an accurate diagnosis can often be made by using a pattern-based approach.